Teachers' reported beliefs about giftedness among twice exceptional and culturally, linguistically, and economically diverse populations - Cody, Rachael A.; Boldt, Gregory T.; Canavan, Elizabeth J.; Gubbins, E. Jean; Hayden, Stacy M.; Bellara, Aarti P.; Kearney, Kelly L. (Frontiers in Psychology, 2022)
The purpose of this research study was to assess the impact of professional learning on teachers’ reported beliefs about students identified as twice exceptional (2e) and students from culturally, economically, and linguistically diverse (CLED) populations, using a semi-randomized experimental design intervention. Teachers in the experimental condition participated in professional learning opportunities featuring curriculum materials, lessons, and activities highlighting support for students identified as 2e or from CLED populations. Teachers in the control condition received no intervention. Across 16 United States’ schools, 53 grade 3 classroom teachers were selected to complete two sets of pre-intervention and post-intervention surveys assessing their reported beliefs about students identified as 2e or from CLED populations. The results indicated that all teachers consistently reported accurate and positive beliefs about the characteristics and needs of these populations, both prior to and after participation in relevant professional learning opportunities. Although analyses revealed main effects of condition and time for certain scales, the reported interaction terms suggested that the professional learning opportunities did not specifically increase questionnaire scores for teachers in the experimental condition. The implications of these findings regarding professional learning and efforts to improve equity in gifted and talented education are discussed.